Chlorination of trichlorosilane/chlorodimethylsilane using metal chlorides: experimental and mechanistic investigations. Issue 12 (9th March 2023) - Duan, Rui; Peng, Wencai; Zhang, Jianshu; Zhang, Jinli
Abstract : Using metal chlorides (WCl6, MoCl5 ) as the chlorine source, the conversion rate of chlorodimethylsilane is much higher than that of trichlorosilane. Abstract : Removal of carbonaceous impurities from trichlorosilane (SiHCl3 ) reduces the carbon content of solar grade polysilicon produced with the improved Siemens method. The separation of chlorodimethylsilane (CH3 )2 SiHCl from SiHCl3 by distillation remains challenging due to the small difference in their boiling points. Herein, the chlorination of (CH3 )2 SiHCl/SiHCl3 with metal chlorides (WCl6, MoCl5 ) were studied. The aim was to convert (CH3 )2 SiHCl into (CH3 )2 SiCl2, increase the relative volatility of (CH3 )2 SiHCl and SiHCl3 and facilitate the distillation. The optimum reaction conditions were 60 °C, 60 min and n (WCl6 or MoCl5 ): n (SiHCl3 or (CH3 )2 SiHCl) = 0.7 at 0.8 MPa. Under these conditions, and when WCl6 and MoCl5 were used as the chlorine sources, the extents of (CH3 )2 SiHCl conversion were 22.7 and 18.5 times higher than those of SiHCl3, respectively. In addition, a mechanistic study showed that the difference between the reactions of SiHCl3 and (CH3 )2 SiHCl resulted from the different energy barriers for the reactions of the and (CH3 )2 SiCl· radicals with WCl x or MoCl x, and the barrier for the reaction was higher than that for the (CH3 )2 SiCl· reaction.